2015
DOI: 10.1371/journal.pone.0125206
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Red Blood Cell-Nitric Oxide Synthase Dependent Nitric Oxide Production during Red Blood Cell Aging in Health and Disease: A Study on Age Dependent Changes of Rheologic and Enzymatic Properties in Red Blood Cells

Abstract: AimTo investigate RBC-NOS dependent NO signaling during in vivo RBC aging in health and disease.MethodRBC from fifteen healthy volunteers (HC) and four patients with type 2 diabetes mellitus (DM) were separated in seven subpopulations by Percoll density gradient centrifugation.ResultsThe proportion of old RBC was significantly higher in DM compared to HC. In both groups, in vivo aging was marked by changes in RBC shape and decreased cell volume. RBC nitrite, as marker for NO, was higher in DM and increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 79 publications
9
69
0
2
Order By: Relevance
“…As mentioned above, in our study, we found that basal RBC-NOS was significantly more activated in uremic erythrocytes than in controls. There are indeed studies indicating that, under several pathological conditions, certain mechanisms that compensate deficient NO production may be activated [25,28,45]. In particular, these mechanisms include plasma oxidative stress, a condition existing in uremia [46,47], which can cause a paradoxical increase in RBC-NOS activity [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, in our study, we found that basal RBC-NOS was significantly more activated in uremic erythrocytes than in controls. There are indeed studies indicating that, under several pathological conditions, certain mechanisms that compensate deficient NO production may be activated [25,28,45]. In particular, these mechanisms include plasma oxidative stress, a condition existing in uremia [46,47], which can cause a paradoxical increase in RBC-NOS activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the RBC pool may be a potentially compensatory intravascular compartment for endothelial dysfunction in diabetes [27]. More recently Bizjak et al [28], by a study on age-dependent changes of rheology and enzymatic properties in RBCs, showed highest RBC-NOS activation and NO production in old RBC, suggesting that this is probably required to counteract the negative impact of cell shrinkage on RBC deformability. In addition, they found this effect even more pronounced in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, garlic has shown the highest NOS stimulating activity [ Table/Fig -2]. In this experimental design, the subjects of Group B were then supplemented with approximately 4 gm (2 cloves) of raw garlic per day for three months, garlic dose recommended in the study by Tattelman E [16] and the University of Maryland Medical Center [17], referred as experimental group II (Group C). At the end of three months of garlic supplementation the subjects of Group C were again subjected to pulmonary function tests.…”
Section: Discussionmentioning
confidence: 99%
“…First, nitrite is formed from the oxidation of nitric oxide (NO) produced by nitric oxide synthase, found in the RBC itself and in endothelial cells (Kleinbongard et al , 2003; Kleinbongard et al , 2006; Cortese-Krott et al , 2012; Grau et al , 2013; Wood et al , 2013; Bizjak et al , 2015). The auto-oxidation of NO to nitrite proceeds slowly ( k = 2×10 6 M −2 s −1 ) compared to oxidation of nitric oxide to nitrate by hemoglobin ( k = 8×10 7 M −1 s −1 ) (Shiva, 2012).…”
Section: Nitrite Acquisitionmentioning
confidence: 99%